Peluang Emas dari Kolam Ikan Nila di Kelompok St. Petrus Lahurus Desa Fatuloti Kecamatan Lasiolat - Andiewati, Suci; Siagian, Gian Asnawi; Gustasya, Yosy; Anwar, Syaeful; Nomleni, Aryok; Turnip, Gilbert; Soares, Daniel Candido Da Costa; Harryes, Regil Kentaurus; Liubana, Debora Victoria (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community Service Activities conducted by aquaculture, Faculty of Military Logistics Vocational, Republic Indonesia Defence University (RIDU) at the St. Petrus Lahurus, Fatuloti Village, Lasiolat District. This activity involved providing knowledge related to techniques, tilapia cultivation efforts, and opportunities for improving education in the fish cultivation sector to support food security. This activity involved the Belu Regency Animal Husbandry and Fisheries Service and the Tilapia Cultivation Group as a manifestation of the implementation of the Tri Dharma of Higher Education. This activity involved the distribution of feed, basic necessities, discussions on cultivation techniques, the presentation of certificates and activity documentation. The activity was interactive and received a positive response from all parties. Furthermore, this activity also provided insights into further education for young tilapia farmers who will continue their education at the Faculty of Military Logistics Vocational, RIDU. The conclusions of this activity emphasized the importance of collaboration between educational institutions, the government, and the community in optimizing local potential to improve economic and social welfare. Recommendations provided included program evaluation, increased collaboration, and further training to strengthen outcomes and ensure program sustainability. This activity increases tilapia productivity efficiently and environmentally friendly, while strengthening synergy between academia and the community for sustainable fisheries and local economic prosperity.